2007
DOI: 10.1002/maco.200604031
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behavior of laser melted AZ91HP magnesium alloy

Abstract: AZ91HP magnesium alloy was melted by CO 2 laser. Compared with as-received Mg alloy, the grain of the melted layer was refined significantly and the content of Al was increased. The corrosion resistance of the melted layer was improved because of the grain refinement, the redistribution of b-Mg 17 Al 12 and the increasing of the Al content. As compared to the non-overlapping zone, the overlapping zone of the melted layer was liable to be corroded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 9 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…These improvements are attributed to the combined influence of grain refinement, dissolution of intermetallic phases and retention of alloying elements in an extended solid solution. Abbas et al [7], Guo et al [8] and Gao et al [9] also observed a similar enhancement of corrosion resistance of laser-melted AZ31, AZ61, WE43 and AZ91 Mg-alloys. Jun et al [10] and Zhang et al [11] mentioned that both microhardness and wear resistance are improved by respectively Nd:YAG pulsed and CO 2 continuous Laser surface melting treatment of the AM50 and AZ91D magnesium alloys.…”
Section: Introductionmentioning
confidence: 49%
“…These improvements are attributed to the combined influence of grain refinement, dissolution of intermetallic phases and retention of alloying elements in an extended solid solution. Abbas et al [7], Guo et al [8] and Gao et al [9] also observed a similar enhancement of corrosion resistance of laser-melted AZ31, AZ61, WE43 and AZ91 Mg-alloys. Jun et al [10] and Zhang et al [11] mentioned that both microhardness and wear resistance are improved by respectively Nd:YAG pulsed and CO 2 continuous Laser surface melting treatment of the AM50 and AZ91D magnesium alloys.…”
Section: Introductionmentioning
confidence: 49%
“…The overlapped region, which was affected by remelting during adjacent laser scan, exhibited a higher corrosion rate. 36 The corrosion behavior of laser-melted AZ91D and AM60B was also investigated. Contrary to the expectations, not much improvement in corrosion resistance was observed for the laser-melted zone.…”
Section: Corrosion Resistancementioning
confidence: 99%
“…The poor corrosion properties of magnesium alloys have resulted in many investigations using LSM to improve the pitting potential. AZ91 has received the most attention [8][9][10] where it was found that LSM dissolves the β-Mg17Al12 precipitate present in the as cast alloy which was responsible for micro galvanic corrosion and the formation of α solid solution of aluminium of up to 10wt%, which provides passive properties to the melted surface. ACM720 has also been investigated [11]and it was found that the rapid solidification of LSM supressed of the formation of Al2Ca phase which is present in the cast alloy in the grain boundaries.…”
Section: Improving the Pitting Potential Of Alloysmentioning
confidence: 99%